2015
DOI: 10.1366/14-07836
|View full text |Cite
|
Sign up to set email alerts
|

Drop-Coating Deposition Raman (DCDR) Spectroscopy as a Tool for Membrane Interaction Studies: Liposome–Porphyrin Complex

Abstract: Drop-coating deposition Raman (DCDR) spectroscopy is based on the measurement of a sample that has been preconcentrated by being dried on a special hydrophobic plate. In addition to its higher sensitivity, the advantage of DCDR over the conventional Raman spectroscopy is the small sample volume needed, the lack of interference from solvents, and the capability of segregating any impurities present and separating components in more complex samples. In this study, DCDR spectroscopy was employed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…As demonstrated in previous studies [ 70 , 71 , 72 ], DCDR analysis showed detection sensitivity superior to conventional Raman for small biological molecules, such as acetylsalicylic acid, riboflavin, and contaminants [ 73 , 74 ], down to a detection limit of 10 −8 M. It also proved to be an important tool for membrane-interaction studies, such as the liposome–porphyrin complex [ 75 ], for the quantitative determination of creatinine in urine [ 76 ], and for colorectal cancer detection in blood plasma [ 77 ]. The advantages of DCDR analysis include the use of dried, preconcentrated samples, a small sample volume, no interference from solvents, and the capability to segregate any existing impurities [ 76 ].…”
Section: Resultsmentioning
confidence: 80%
“…As demonstrated in previous studies [ 70 , 71 , 72 ], DCDR analysis showed detection sensitivity superior to conventional Raman for small biological molecules, such as acetylsalicylic acid, riboflavin, and contaminants [ 73 , 74 ], down to a detection limit of 10 −8 M. It also proved to be an important tool for membrane-interaction studies, such as the liposome–porphyrin complex [ 75 ], for the quantitative determination of creatinine in urine [ 76 ], and for colorectal cancer detection in blood plasma [ 77 ]. The advantages of DCDR analysis include the use of dried, preconcentrated samples, a small sample volume, no interference from solvents, and the capability to segregate any existing impurities [ 76 ].…”
Section: Resultsmentioning
confidence: 80%
“…The main advantage was a perfect accumulation of liposomes in the ‘coffee‐ring’ without remarkable loss of the lipid structural arrangement and a complete separation of smaller molecules or molecular complexes not bound to liposomes. This permits the DCDR method to observe interacting molecular systems present at low percentages in the original liposome suspension 32 …”
Section: Dcdr Studies Of Biomolecules and Biologically Important Mole...mentioning
confidence: 99%
“…This permits the DCDR method to observe interacting molecular systems present at low percentages in the original liposome suspension. 32 To improve DCDR performance even more, we performed substantial studies concerning new substrates for DCDR. In addition to the available commercial and noncommercial substrates, attempts to prepare novel hydrophobic substrates in an easy and low cost way were made.…”
Section: Dcdr Studies Of Biomolecules and Biologically Important Mole...mentioning
confidence: 99%
“…Drop-casting and dried samples A widely used approach for preparing liquid samples for Raman measurements is application by (micro)pipette and allowing to air-dry on a supporting surface. [12,106,107,131,262,263] This is known as the "drop-casting" method and is viewed as a quick and easy approach within Raman studies. [264] The technique often results in a highly non-uniform distribution of fluid constituents across the dried spot area due to the evaporation gradient and consequent capillary forces acting on the drying droplet.…”
Section: Storagementioning
confidence: 99%
“…If accurate quantitative analysis is required, the exact regions being measured will need to be carefully identified. [60,262] In some cases, the "coffee rings," or more precisely, radial surface distributions, can be beneficial, [12,262,[267][268][269][270] having been used for facilitating the detection of various biomolecules, [263,[271][272][273][274][275] and used for concentrating or spatially separating the desired salivary constituents. [276,277] In a proteomic study, Zhang et al [270] showed that such ring formations remain stable for weeks.…”
Section: Storagementioning
confidence: 99%